KONSTRUKSI PASIF BAHASA JEPANG (Kajian Gramatika Relasional) - Rita Maria Sahara; Lien Darlina (Politeknik Negeri Bali, 2013)
This article examines of Japanese passive construction viewed from a study of relational grammar. Passive construction in Japanese are divided into three types, namely chokusetsu ukemi 'direct passive', mochinushi no ukemi 'possession passive', and daisansha no ukemi 'third party passive'. By applying Relational Grammar Theory (RG), the result of analysis indicates that the changes of grammatical relation has the same revaluation in ukemi chokusetsu, that is the direct object of active construction becomes the subject of passive and active construction subject becomes chomeur. In Japanese, mochinushi no ukemi, and daisansha no ukemi can be operated by RG with its own constraints.